SARS-CoV-2 Immuno-Pathogenesis and Potential for Diverse Vaccines and Therapies: Opportunities and Challenges - Andrew R. McGill; Roukiah Khalil; Rinku Dutta; Ryan Green; Mark Howell; Subhra Mohapatra; Shyam S. Mohapatra (MDPI AG, 2021)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is a novel coronavirus that emerged from Wuhan, China in late 2019 causing coronavirus disease-19 (COVID-19). SARS-CoV-2 infection begins by attaching to angiotensin-converting enzyme 2 receptor (ACE2) via the spike glycoprotein, followed by cleavage by TMPRSS2, revealing the viral fusion domain. Other presumptive receptors for SARS-CoV-2 attachment include CD147, neuropilin-1 (NRP1), and Myeloid C-lectin like receptor (CLR), each of which might play a role in the systemic viral spread. The pathology of SARS-CoV-2 infection ranges from asymptomatic to severe acute respiratory distress syndrome, often displaying a cytokine storm syndrome, which can be life-threatening. Despite progress made, the detailed mechanisms underlying SARS-CoV-2 interaction with the host immune system remain unclear and are an area of very active research. The process's key players include viral non-structural proteins and open reading frame products, which have been implicated in immune antagonism. The dysregulation of the innate immune system results in reduced adaptive immune responses characterized by rapidly diminishing antibody titers. Several treatment options for COVID-19 are emerging, with immunotherapies, peptide therapies, and nucleic acid vaccines showing promise. This review discusses the advances in the immunopathology of SARS-CoV-2, vaccines and therapies under investigation to counter the effects of this virus, as well as viral variants.